The Impact Of Visual Feedback In Improving Technical Performance And Athlete Achievement Of Long Jump Efficiency To Athletes Students - Barkati, Nasereddin (جامعة الوادي - University of Eloued, 2023)
identifying the importance of a proposed programme in improving the technical performance and the athlete achievement of long jump efficiency to athlete students. The researcher used the experimental method by designing two groups; the experimental and the regulator with two parameters; the before and the after which fit the nature of the study on a sample consisted of 3rd. The study showed that the instructional programme which is based on feedback has an impact in improving the technical and kinetic performance of long jump and in the athlete’s performance and achievement. معرفة أهمية البرنامج المقترح المبني على التغذية الراجعة المرئية في تحسين الأداء الفني و الانجاز الرياضي لفعالية الوثب الطويل لدى طلبة تخصص العاب القوى ، اعتمد الباحث المنهج التجريبي لملاءمته لطبيعة الدراسة، على عينة متكونة من طلبة السنة الثالثة تخصص العاب القوى، توصلت الدراسة إلى : للبرنامج التعليمي المبني على التغذية الراجعة أثر في تحسين الأداء الفني والحركي لفعالية الوثب الطويل في الأداء والانجاز الرياضي واعتمد.
article
Keywords: visual feedback, long jump, athlete performance; التغذية الراجعة المرئية ، الوثب الطويل – الأداء و الانجاز الرياضي